PEMBANGKIT LISTRIK TENAGA ANGIN DENGAN INOVASI TURBIN HELIKS VERTIKAL UNTUK KEMANDIRIAN ENERGI SEKOLAH DAERAH PESISIR - Bagar, Kamal Habibi; Wicaksono, Wahyudi; Rohmadin, Novem Ardan; Prasetyawan, Adi; Rahman, Arief (Program Kreativitas Mahasiswa - Teknologi, 2013)
Indonesian coastal have wind great potential because it has the second longest coastline in the world. In contrast to conventional wind turbines can only absorb a maximum of about 30 % of wind energy, wind tur-bine theoretically and practically helices can absorb almost 40-50 % and convert it into mechanical energy due to the helical blade design that uses the principle of lift force and torque on the blades distribution, so it is very advantageous to be applied to the coastal regions of Indonesia. By combining the generator dual axi-al and helical turbine power can be generated with a range of about 500 Watts . One of the schools in the area Cumpat Kenjeran Surabaya chosen as a partner because of the location of the school adjacent to the coast followed by the electrical energy needs for learning tools such as computers , tools and other lab work. To manufacture helical blade assisted by PT Mitra Mandiri Perkasa which help in the problem of providing tools .